An enantiopure N,N,S scorpionate ligand derived from (+)-camphor - Godau, Tom; Platzmann, Florian; Heinemann, Frank Wilhelm; Burzlaff, Nicolai (Dalton Transactions, 2009)
Reductive S-S bond cleavage of a disulfide precursor 3 obtained from a pyridine-catalyzed Peterson-type reaction starting from camphorpyrazole 1, thionyl chloride and 2-methyl-2-(methyldithio)propionaldehyde yields 2,2′-bis(camphorpyrazol-1-yl)-2-methylpropane-2-thiol (HS prbpm, 4); the first zinc complexes bearing this ligand exhibit κ coordination of the ligand. © 2009 The Royal Society of Chemistry.